2016
DOI: 10.1093/intqhc/mzw062
|View full text |Cite
|
Sign up to set email alerts
|

Vital signs monitoring on general wards: clinical staff perceptions of current practices and the planned introduction of continuous monitoring technology

Abstract: While continuous monitoring devices were seen as a potentially positive tool to support the identification of patient deterioration, drawbacks, such as the potential for reduced patient contact, revealed key areas that will require close surveillance following the implementation of devices. Training and improved interdisciplinary communication were identified as key requisites for successful implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
105
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(117 citation statements)
references
References 34 publications
10
105
0
2
Order By: Relevance
“…Nursing teams were appreciative of the technology used. We are aware that especially with regards to continuous monitoring these finding might not be generalizable [27, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…Nursing teams were appreciative of the technology used. We are aware that especially with regards to continuous monitoring these finding might not be generalizable [27, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…Five studies reported nursing perception (Banks et al, 1999;Jeskey et al, 2011;Langhorne et al, 2010;Prgomet et al, 2016;Watkins et al, 2015) and all identified similar themes.…”
Section:  Nursing Perceptionmentioning
confidence: 94%
“…Nurses perceived that greater 'availability and accessibility' of vital signs information would support their decisionmaking and provide reassurance to patients. (Prgomet et al, 2016) The value of continuous monitoring was particularly evident to nurses who were trained and felt confident in its use, (Jeskey et al, 2011;Langhorne et al, 2010) while lack of familiarity with the technology was associated with loss of engagement and the perception of increased workload. (Banks et al, 1999) Banks et al stress the importance of training in time allocated away from clinical duties.…”
Section:  Nursing Perceptionmentioning
confidence: 99%
See 2 more Smart Citations